Metagenomic analysis of blood microbiota alterations: insights into HIV progression and immune restoration - Chen, Yingjie; Zhang, Rongqiu; Wen, Juan; Zhao, Jingyue; Zhang, Jianmei (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionEmerging evidence suggests that the blood microbiome may influence the progression of HIV infection and immune restoration. This study aims to comprehensively characterize blood microbiota alterations associated with HIV infection and antiretroviral therapy (ART), and to evaluate their potential as microbial indicators for assessing infection status and immune restoration.MethodsWe recruited 91 participants, including 31 treatment-naïve HIV-infected individuals, 30 ART-treated individuals with undetectable viral loads, and 30 healthy controls. Blood samples were collected for metagenomic sequencing and immunological profiling.ResultsHIV infection profoundly disrupted blood microbiota diversity and composition, with a marked reduction in α-diversity and enrichment of opportunistic pathogens such as Pseudomonas aeruginosa, Acinetobacter baumannii and Stenotrophomonas maltophilia, alongside depletion of beneficial taxa like Bifidobacterium longum. ART partially restored microbial diversity but did not fully reestablish a healthy microbiota. Correlation analysis revealed that Acinetobacter pittii, Xanthomonas campestris and Diaphorobacter nitroreducens were significantly associated with viral load, suggesting their potential role in HIV progression. Additionally, after ART, Acinetobacter junii and Pseudomonas putida were significantly correlated with the CD4/CD8 ratio, indicating their potential role in immune restoration.DiscussionThese findings provide new insights into the interactions between blood microbiota and HIV progression. The identified blood microbiota may serve as potential indicators for evaluating HIV infection status and treatment efficacy, offering a basis for microbial-based diagnostic and therapeutic strategies.